-5-x(x-7)+6x=-1

Simple and best practice solution for -5-x(x-7)+6x=-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5-x(x-7)+6x=-1 equation:



-5-x(x-7)+6x=-1
We move all terms to the left:
-5-x(x-7)+6x-(-1)=0
We add all the numbers together, and all the variables
6x-x(x-7)-4=0
We multiply parentheses
-x^2+6x+7x-4=0
We add all the numbers together, and all the variables
-1x^2+13x-4=0
a = -1; b = 13; c = -4;
Δ = b2-4ac
Δ = 132-4·(-1)·(-4)
Δ = 153
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{153}=\sqrt{9*17}=\sqrt{9}*\sqrt{17}=3\sqrt{17}$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(13)-3\sqrt{17}}{2*-1}=\frac{-13-3\sqrt{17}}{-2} $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(13)+3\sqrt{17}}{2*-1}=\frac{-13+3\sqrt{17}}{-2} $

See similar equations:

| x+35=2x-15 | | -3x(-x+7)+5x=-21 | | J(x)=3x+18/6 | | 15÷(x-3(-3)x=-2 | | 180=(5×+4)(4x-4) | | (1/2)(9.8)t^2+9.3(0.4226182617)t-10=0 | | 6+2/7r=-6 | | r+30=1 | | (2x–1)(x+3)=4 | | X+44+x=44 | | p-15=-48 | | |2-4x|+8=22 | | 7x-6=99 | | z/7+9=7 | | 5x+2(4x-19)=-21 | | z/9+6=-1 | | 1=(5+n)/9 | | 2x+35=x-11 | | 36+9/5r=-36 | | 15÷(x-3)x=-2 | | 10=x-(-12) | | 432=m-391 | | 1/3y+2.3=3y+2 | | 6=2(3j-2)=4(1+j) | | D-4+3d-7=5 | | 6x-4+4x+4=180° | | Y=30x/6x | | (X+60)2-((x+50)+60)=210 | | -2x-(-5)x=-3 | | 13=c=54 | | 31a-2=4a+45+4a+45 | | 5x-3•(-3)=15 |

Equations solver categories